2010
DOI: 10.1093/nar/gkq922
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic block copolymers enhance the cellular uptake of DNA molecules through a facilitated plasma membrane transport

Abstract: Amphiphilic block copolymers have been developed recently for their efficient, in vivo transfection activities in various tissues. Surprisingly, we observed that amphiphilic block copolymers such as Lutrol® do not allow the transfection of cultured cells in vitro, suggesting that the cell environment is strongly involved in their mechanism of action. In an in vitro model mimicking the in vivo situation we showed that pre-treatment of cells with Lutrol®, prior to their incubation with DNA molecules in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…These muscle-specific miRNAs and known to be differentially expressed in adult skeletal muscle tissue (34). To transfect the skeletal muscles efficiently the RILES plasmids were formulated with the amphiphilic block copolymer 704 (704) as described in (29) and then intramuscularly administered in the two tibialis anterior muscles of naive mice. Six days later (Figure 4A) strong bioluminescence signals were detected in the lower legs of mice administered with pRILES bearing the myomiRNA targeting cassette 1T, -133T and -206T.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These muscle-specific miRNAs and known to be differentially expressed in adult skeletal muscle tissue (34). To transfect the skeletal muscles efficiently the RILES plasmids were formulated with the amphiphilic block copolymer 704 (704) as described in (29) and then intramuscularly administered in the two tibialis anterior muscles of naive mice. Six days later (Figure 4A) strong bioluminescence signals were detected in the lower legs of mice administered with pRILES bearing the myomiRNA targeting cassette 1T, -133T and -206T.…”
Section: Resultsmentioning
confidence: 99%
“…Female, 8-week-old outbred Swiss mice (BALB/c genetic background) and athymic nude mice were obtained from Harlam (France). Intramuscular injections of expression plasmids were performed as previously described: 8 µg expression plasmid or 2 µg inducible expression plasmid plus 6 µg pQE30 plasmid formulated with the amphiphilic block copolymer 704 (29) were administered into the tibialis anterior muscles of mice. Hydrodynamic injections were prepared in a saline physiological buffer corresponding to 10% body volume of the mouse and were administered over a 5-s period into the tail vein of mice (30).…”
Section: Methodsmentioning
confidence: 99%
“…This new type of complexation may be interesting for the orientation of lipoplexes in view of improving their stability in the presence of serum and of improving the transfection The Journal of Physical Chemistry B Article efficiency of Lx. 9,51,52 They could also promote a singular endocytosis path for the transport of gene material through the cell membrane.…”
Section: But Wementioning
confidence: 99%
“…To this end, Chevre et al have reported that Lutrol ® , with 80% PEO, enhances gene delivery by promoting plasma membrane transport via direct fusion, and amphiphilic polymer P85 with 50% PEO promotes DNA transfection in a promoter-dependent manner and activates the NF-kB signaling pathway. 52 Furthermore, the state of aggregation of Pluronic chains in aqueous solution (unimer or micelle) affects the route of endocytosis. For example, P85 unimers were shown to enter cells by caveolae-mediated of endocytosis, while P85 micelles enter by clathrin-mediated endocytosis in the model MDCK (Madin-Darby canine kidney) cells.…”
Section: Poly (Alkylene Oxide) Copolymers As Adjuvant Agents To Nakedmentioning
confidence: 99%